Experience and Prospects of Artificial Intelligence Technologies Application in the Film Industry - Юлія Трач (Цифрова платформа: інформаційні технології в соціокультурній сфері, 2022)
The purpose of the research is to summarize the experience and outline the prospects for the application of artificial intelligence technologies in the film industry.